The "Securitization" theory and the problem of political rhetoric in social networks (Herald of Journalism, 2022)
In the usual sense, "information security" means a set of measures necessary to protect against leakage or hacking of computer systems, programs and data. However, recently the concept of security has begun to change - in connection with this, the approach to the concept of information security has begun to be filled with new social and political meanings. Cyberspace is a defining feature of modern life.Therefore, the concept of "national security" began to extend in terms of "Cyber Security Politics", concept including new reference objects, such as Internet networks and messengers, socio-political threats and challenges. The emergence and development of this approach was largely influenced by the theory of speech acts of the Copenhagen School "securitization" concept.The main purpose of the study is to determine how "cybersecurity" is connected in general with the theory and practice of state security policy, to determine the role of politicians and media specialists’ rhetoric in social media, in election campaigns; and to show the methods of speech acts influence on ensuring and maintaining information/Internet security.Based on content analysis and discursive analysis of speech acts used in social media such as Facebook, Twitter and others, the following results were obtained: the importance of posing the problem of the social threat of social media to the formation of mass consciousness is indicated, the need to solve the problem at the legislative level is pointed.Cybersecurity threats are one of the main national security, public safety, politics and economy challenges every nation faces in XXI century. The existence of numerous cyber security issues on various spheres of life naturally increase political interest in resolving them.The novelty of the study lies in the analysis of the Kazakhstani segment of the Internet, comparative analysis with problematic cases of cyber threats in the USA and Russia. The results of the study are of practical importance for the media professionals, content managers of social media, in order to mainain the Internet security.Keywords: cybersecurity, concept of “securitization”, preventing threats and challenges of a socio-political nature, social media, rhetoric.